Managing the information technology resources leadership in the information age - Luftman, Jerry N.; Bullen , Christine V. (Pearson Education, 2004)
This book prepares readers for the challenge of integrating the technology resource. In order to understand the industry today, one must understand the ways companies align, partner, and communicate through technology to grow their business. Managing the Information Technology Resource presents a set of powerful tools to ensure users' understanding of the strategies, tactics, and operational endeavors CIO's employ to assimilate technologies across the firm. ¿Examples in Action¿ boxes highlight real-world company examples in each chapter, lending a practical feel to the book so readers can see how this material relates to the actual workforce. Seven sections illustrate the critical topics inherent to IT in today's firm--Alignment, Partnership, Technology, Human Resources, Governance, Communications, and Metrics. Emphasis is placed on the tactical and operational role of the CIO. For anyone involved with IT in a company. -- Product Description.